Nieformalne ścieżki uczenia się języka polskiego jako obcego wśród studentów frankofońskich na przykładzie Uniwersytetu w Poitiers - Zygadło, Dorota (Neofilolog, 2026)
Polish, considered in France as a Less Widely Used and Less Widely Taught (LWULT) language, is taught mainly in academic contexts and often with limited access to dedicated resources. This situation makes informal learning particularly significant for students who wish to strengthen their competence beyond the classroom. This article examines informal practices of Francophone students at the University of Poitiers, focusing on how they engage with Polish outside formal instruction. The analysis highlights a variety of activities, including the use of mobile applications, exposure to audiovisual materials, participation in social media, and occasional personal contacts with the language. These practices are embedded in the broader framework of formal, non-formal, and informal learning as outlined in the CEFR and subsequent research. The study emphasizes that, for LWULT languages such as Polish, informal learning complements academic courses, ensures regular exposure to authentic language use, and fosters cultural engagement. It also underlines the importance of the teacher’s role as a mentor who helps students navigate available resources and develop autonomous strategies for language learning.